2014
DOI: 10.1002/ange.201406097
|View full text |Cite
|
Sign up to set email alerts
|

Bildung und Umlagerung von Homoserin‐Depsipeptiden und ‐proteinen durch α‐Ketosäure‐Hydroxylamin‐Ligation mit 5‐Oxaprolin

Abstract: Die Hauptprodukte der chemischen Ligation von aKetosäuren und 5-Oxaprolin sind Ester und nicht -wie zuvor berichtet -Amide. Durch die schnell ablaufende Umlagerung in basischen Puffern lässt sich das Depsipeptidprodukt in das Amid überführen. Die Esterbildung ermçglicht Rückschlüsse auf den mçglichen Mechanismus von Typ-II-KAHA-Ligationen und erçffnet einen Weg zur chemischen Synthese von Depsiproteinen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…During studies in dipeptide model systems, it was found that ligations with 5-oxaproline give unexpectedly the depsipeptide with an ester linkage rather than the anticipated amide (Scheme 28, see also mechanism in the section "Type II") [26,27]. Conveniently, these depsipeptides are readily rearranged to the amides in basic buffers.…”
Section: Formation and Rearrangement Of Depsipeptidesmentioning
confidence: 96%
See 1 more Smart Citation
“…During studies in dipeptide model systems, it was found that ligations with 5-oxaproline give unexpectedly the depsipeptide with an ester linkage rather than the anticipated amide (Scheme 28, see also mechanism in the section "Type II") [26,27]. Conveniently, these depsipeptides are readily rearranged to the amides in basic buffers.…”
Section: Formation and Rearrangement Of Depsipeptidesmentioning
confidence: 96%
“…Chemical Protein Synthesis with the KAHA Ligation reaction is the ester and not the expected amide [26,27]. Most likely, the alcoholwhich is released upon decarboxylation -can intercept the intermediate nitrilium in an intramolecular addition.…”
Section: Scheme 4 Mechanism For Type I Ligationsmentioning
confidence: 98%